O dwóch pociągach i dwóch morderstwach - Kaczmar, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of this article is to familiarize the reader with problems connected with a train as a scene of murder in selected novels by Agatha Chrisitie and Kerry Greenwood. This considerations are about the specificity of a train as an area. It further indicates the significance of this means of transport as a perfect murder scene. The article shows the type of the main character of these stories - the detective, by means of a contrastive analysis of these two novels.
Keywords: pociągi; morderstwo; przestrzeń; morderca; detektyw; ofiara; zbrodnia; kryminał; trains; murder; area; killer; detective; victim; crime; crime story